2011
DOI: 10.2139/ssrn.1813744
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy and Retirement Planning in Germany

Abstract: We examine financial literacy in Germany using data from the SAVE survey. We find that knowledge of basic financial concepts is lacking among women, the less educated, and those living in East Germany. In particular, those with low education and low income in East Germany have little financial literacy compared to their West German counterparts. Interestingly, there is no gender disparity in financial knowledge in the East. In order to investigate the nexus of causality between financial literacy and retiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
5
34
0
1
Order By: Relevance
“…As pointed out by Lusardi and Mitchell (2014), most studies find that the OLS estimate of the impact of financial literacy is biased downward, but the estimates differ a lot across papers, and the magnitude of the bias varies largely in the literature. The instrumental variable estimates range from three times larger than the corresponding OLS estimates (Jappelli and Padula, 2013b;van Rooij et al, 2012) to thirteen times larger than OLS (Bucher-Koenen and Lusardi, 2011). Our findings confirm the downward bias of the OLS estimate, showing that the causal effect is four times larger.…”
Section: Related Literaturesupporting
confidence: 72%
See 1 more Smart Citation
“…As pointed out by Lusardi and Mitchell (2014), most studies find that the OLS estimate of the impact of financial literacy is biased downward, but the estimates differ a lot across papers, and the magnitude of the bias varies largely in the literature. The instrumental variable estimates range from three times larger than the corresponding OLS estimates (Jappelli and Padula, 2013b;van Rooij et al, 2012) to thirteen times larger than OLS (Bucher-Koenen and Lusardi, 2011). Our findings confirm the downward bias of the OLS estimate, showing that the causal effect is four times larger.…”
Section: Related Literaturesupporting
confidence: 72%
“…However, van Rooij et al (2012) are skeptical about the validity of the exclusion restriction for the instrumental variable they use, and they discuss the issue at length in the paper, adding a rich set of controls to their baseline specification. Other studies hinge on the idea that the respondent's financial literacy is influenced by financial knowledge of peers or reference groups Bucher-Koenen and Lusardi, 2011;Fornero and Monticone, 2011;Jappelli and Padula, 2013a;Klapper et al, 2013;Klapper and Panos, 2011;van Rooij et al, 2012). The assumption that lies behind this identification strategy is that the respondent cannot influence the peers' experience significantly, i.e., there is no "reflection problem" (Manski, 1993).…”
Section: Related Literaturementioning
confidence: 99%
“…Earlier studies have shown that financial literacy has a positive effect on long-term savings and retirement planning (Lusardi andMitchell, 2007, Clark et al, 2012), stock market participation (van Rooij et al, 2011a), portfolio diversification (Guiso and Jappelli, 2008), wealth (Gustman et al, 2012, van Rooij et al 2012, Jappelli and Padula, 2013, and informed use of debt (Lusardi andTufano, 2009, Stango andZinman, 2009). Results in Section 5 and 6…”
Section: The Impact Of Financial Literacy On Financial Decisionsmentioning
confidence: 99%
“…One test was conducted in February 2013 -prior to the initial start of the program, called pre-test-and the second one was conducted after the full development of Level I in May 2013 -the post-test. 9 Schools in the evaluation sample gave the material in the third year of high school only. In addition, students in the fourth year of high school went through the same set of …nancial literacy tests but were not taught the …nancial literacy material.…”
Section: Evaluation In 2012-2013mentioning
confidence: 99%
“…9 To ensure comparability of results between the pre-test and post-test, two parallel forms (A and B) were constructed. In the pre-test each form consists of 30 items: 20 are common, and 10 items are speci…c to each form.…”
Section: Evaluation In 2012-2013mentioning
confidence: 99%